Zagadnienia Doświadczalnej Weryfikacji Modelu Ciała Rozdrobnionego o Wzmocnieniu Gęstościowym - Drescher, A. (Engineering Transactions, 1972)
The paper bears the character of a review and presents the assumptions, the mathematical relations and their physical interpretation for a model of granular medium with a density hardening proposed by Z. MRÓZ. The model describes the fundamental properties of granular media in a wide range of deformation including the coupling of shearing and voluminal strains and also the dependence of plastic properties upon the density of the medium. The detailed analysis of the behaviour of the model subject to simple and complex loading paths is limited to the rigid-plastic model. The methods of experimental verification and of determination of the material functions are also given. The considerations are illustrated by the examples in which the material functions were determined on the basis of experiments with triaxially compressed dry sand. It is shown that a sufficient accuracy may be obtained by assuming the associated flow rule and the yield surface whose cross-section by the (σ1, √2 σ2)-plane has the form of a straight line segment and ellipse, depending linearly on the density.